Nutritional Status in Children with End-Stage Kidney Disease Undergoing Hemodialysis and Other Related Factors - Namira Metasyah; Eka Laksmi Hidayati (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: Chronic kidney disease causes several changes in the body's function in metabolizing nutrients. This has led to the discovery of cases of malnutrition in chronic kidney disease patients, especially in ESRD patients undergoing hemodialysis. This certainly needs to be a concern because nutrition is very important for children's growth. Therefore, this study was conducted to find out the effect of hemodialysis and other influencing factors on the nutritional status of children. Methods: The study was conducted with a cross- sectional design by taking secondary data in the form of disease stage, duration of disease, primary etiologic factors, and comorbidities from medical records. Data on the nutritional status of children was obtained by measuring weight and height, and upper arm circumference and then entered into the WHO Anthro application. Demographic data, such as the education level of the father & mother, family economic status, age, and gender were obtained by filling out the Case Report Form (CRF). Twenty respondents met the inclusion and exclusion criteria of this study. Results: The average nutritional status assessment seen from the body mass index according to age showed results of -2 SD < x < 1 SD with good nutrition interpretation and x <-2 SD (short stature) in terms of height according to age. Based on bivariate analysis, there was no significant effect between duration of hemodialysis, frequency of hemodialysis, etiology, age, sex, and comorbidities (p>0.05) in children with chronic kidney failure who were undergoing hemodialysis on their nutritional status. Conclusion: The nutritional status of CKD children undergoing hemodialysis was assessed based on body mass index and height according to age. The average results were good nutrition but with short stature. There was no effect of duration, frequency, etiology, age, gender, and comorbidities in children with chronic kidney failure undergoing hemodialysis on their nutritional status.